The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/13696998.2020.1737536
|View full text |Cite
|
Sign up to set email alerts
|

The burden of osteoporosis in Saudi Arabia: a scorecard and economic model

Abstract: 1 exp Osteoporosis/ (165703) 2 osteoporo*.tw,kf. (169279) 3 bone loss*.tw,kf. (58197) 4 Bone Density/ (133563) 5 (bone? adj3 densit*).tw,kf. (120995) 6 bmd.tw,kf. (70147) 7 Bone Diseases, Metabolic/ (9391) 8 Bone Demineralization, Pathologic/ (2467) 9 (bone? adj3 (calcifi* or deminerali*)).tw,kf. (9768) 10 or/1-9 [OSTEOPOROSIS] (347408) 11 Saudi Arabia/ (28321) 12 saudi arabia?.tw,kf,cp,gc,hw,in. (153849) 13 United Arab Emirates/ (4284) 14 (Emirates or United Arab Emirat* or UAE).tw, kf,cp,gc,hw,in. (55876)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…Among patients with fractures, our study revealed that the PPPY cost could reach up to USD 31,249.16 for patients undergoing surgeries, including hip replacement, and fractures largely drove the costs of procedures, physiotherapy, and hospitalization. This finding is astronomically higher than the costs reported by previous local studies that ranged from USD 12,868 to USD 20,000 [ 14 , 19 ]. This indicates that the economic burden associated with osteoporosis-related fractures is significant and was previously underestimated.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Among patients with fractures, our study revealed that the PPPY cost could reach up to USD 31,249.16 for patients undergoing surgeries, including hip replacement, and fractures largely drove the costs of procedures, physiotherapy, and hospitalization. This finding is astronomically higher than the costs reported by previous local studies that ranged from USD 12,868 to USD 20,000 [ 14 , 19 ]. This indicates that the economic burden associated with osteoporosis-related fractures is significant and was previously underestimated.…”
Section: Discussioncontrasting
confidence: 52%
“…The average direct annual cost of osteoporosis in the U.S., Canada, and Europe was estimated to be between USD 5000 and USD 6500 billion [ 18 ]. In Saudi Arabia, the direct cost of osteoporosis-related femoral fractures was estimated at USD 150.60 million, while the total economic burden of osteoporosis-related fractures was estimated to be around USD 3.60 billion [ 14 , 19 ]. Osteoporosis-related hospitalization, followed by diagnosis testing and medications, was found to be the major driver of direct costs related to osteoporosis in Saudi Arabia [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a serious risk factor for bone fracture [25], which has a large medical cost [26,27] and social burden [28]. Some countries have established bone fracture reporting systems to mitigate these costs [29]. Taiwan has also established a medical network for preventing and treating osteoporosisinduced bone fracture [30].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is the most common silent disease with the thirdhighest incidence in the aging population. 1 The important public health problem has added an increased incidence of fractures, disabilities, deprived quality of life with increased mortality in the aging population of developing countries. [1][2][3] Bone turnover is the process of bone resorption followed by replacement by new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…1 The important public health problem has added an increased incidence of fractures, disabilities, deprived quality of life with increased mortality in the aging population of developing countries. [1][2][3] Bone turnover is the process of bone resorption followed by replacement by new bone formation. Osteoclast and osteoblast are the main cells involved in this process.…”
Section: Introductionmentioning
confidence: 99%